HASIL BELAJAR LOMPAT JAUH MELALUI POLA BERMAIN MENGGUNAKAN SIMPAI SISWA KELAS V SD (Department of Physical Education, Sport, Health and Recreation, 2013)
AbstrakLompat jauh merupakan salah satu nomor dalam cabang olahraga atletik yang diajarkan pada siswa. Sekolah Dasar. Namun dalam proses pembelajaran belum terlaksana secara optimal. guru perlu merencanakan suatu model pembelajaran yang menarik bagi siswa dan dapat mengembangkan potensi siswa. Salah satunya permainan lompat jauh menggunakan simpai. Penelitian ini menggunakan desain penelitian tindakan kelas. Pelaksanaan penelitian ini tindakan kelas ini dilakukan dalam dua siklus yaitu siklus I dan siklus II. Setiap siklus terdiri atas empat tahap, yaitu perencanaan, tindakan, observasi, dan refleksi. Hasil belajar yang dinilai adalah aspek kognitif, afektif dan psikomotor. Hasil penelitian dari siklus I ke Siklus II belajar kognitif 77,46, afektif 82,29 dan psikomotor 78,73. Hasil ini sudah mencapai batas minimal ketuntasan yaitu 70.Berdasarkan data hasil penelitian, disimpulan bahwa permainan lompat jauh menggunakan simpaidapat meningkatkan hasil belajar siswa.AbstractThe students of elementary school at SD N Tambak Aji 04 has barriers to join sport activity, especially on the subject of learning sprint. Students tend tobe more passive in teaching physical education. The result of this problem is limited movement of the student. Hence the need for modifications in the learning process. The method of research is developing. The procedures of product development includes needs analysis, develop initial product, the evaluation by experts, the first product revision, field tests, revision of the final product, the final fortress game model for learning sprinting on fifth grade elementary school students. The data was collected using field observations and question naires were obtained from expert evaluation. The data analysis technique used is descriptive percentages. From the test results obtained by the expert evaluation data, expert Penjasorkes 87.5% (good), a lesson I 81.3% (good), a learning II 97.3% (very good). Moderate data from small-scale trials psychomotor aspects of 82.5% (good), cognitive 90.5% (very good), affective 92.5% (very good) and the large-scale trials psychomotor aspects 90% (good), Cognitive 91.9% (very good), affective 89.5% (good). From these results it can be concluded fortress game model for learning sprint worth using. With the development of effective pernjasorkes learning outcomes of fifth grade at SD N tambak aji 04.